Understanding of strain-induced crystallization developments scenarios for polyesters: Comparison of poly(ethylene furanoate), PEF, and poly(ethylene terephthalate), PET - Forestier, Emilie; Combeaud, Christelle; Guigo, Nathanael; Sbirrazzuoli, Nicolas; Billon, Noelle (Polymer (Guilford), 2020)
Specific conditions of strain, stretching, strain rate and temperature are known to be necessary for the strain induced crystallization phenomenon (SIC) to occur. It leads to the formation of a crystal in different amorphous polymers, stretched above their glassy transition. This phenomenon was intensively documented in case of poly(ethylene terephthalate), PET. More recently, some studies focused on SIC development in biobased poly(ethylene furandicarboxylate), PEF. Comparison of these crystallization abilities and crystallization kinetics upon stretching in the two materials allows to describe main differences between them, and to enlighten the role of chain architecture on SIC. To achieve that point, different mechanical tensile tests were conducted using well controlled loading paths to explore the different steps of the microstructural changes induced by the stretching and their correlation with mechanical behaviour. Several macroscopic equivalence in the effects of SIC were found, such as increase in modulus, appearance of organized phase, increase I n α−relaxation temperature despite some differences in chain architecture. Combining both loading-unloading tests and quenching protocols, it was found that inducing more or less strong interactions between constitutive units, and more or less stable crystalline phases, leads to differences in apparent strain induced crystallization kinetics: • PET stretching can induce, prior to main strain hardening step, the formation of re-enforcing intermediate phases (or imperfect crystal) being stable upon unloading and able to be improved upon relaxation or thermal treatments; • PEF stretching exhibits a more “simple” two-steps path with no intermediate phases stable upon unloading. This can be related with the weaker stability of PEF crystal compared to PET (PEF quiescent crystallization temperature and melting temperature are very close to each other), and to the more complex crystalline lattice in PEF (two units are needed instead of one due to furanic cycle). In addition, for PET, Young modulus increases more gradually during strain hardening than for PEF. The final microstructure after stretching is therefore more dependent on thermomechanical treatments (annealing or relaxation steps) in PET in comparison to PEF. [Display omitted] •Stretch ability of PEF.•Stretch ability of PET.•Strain induced crystallization of PEF.•Strain induced crystallization of PET.